Remembering the German Democratic Republic
XIV, 308 p.
Keywords: Memories of and attitudes to the German Democratic Republic (GDR), or East Germany, within contemporary Germany are characterized by their variety and complexity, whilst the debate over how to remember the GDR tells us a lot about how Germans see themselves and their future. This volume provides a range of international perspectives.